Validity and Reliability of Online Socio-Scientific Issue-Based Critical Reasoning Instrument - yokhebed, yokhebed; Sutarno, Sutarno; Masykuri, Mohammad; Adi Prayitno, Baskoro; sudirman , sudirman (Universitas Negeri Semarang, 2024)
Information regarding the evaluation of reasoning skills related to online socio-scientific issues is still limited due to limited instruments. This research aims to determine the validity and reliability of an online socio-scientific issue-based critical reasoning instrument. Content validity was proven by the assessment method by five experts. Confirmatory factor analysis was carried out with the Lisrel 8.8 program to prove construct validity. Instrument testing was carried out on 145 grade 10 high school students. Convergent validity was determined through the Average Variance Extracted (AVE) calculation, and reliability was determined through Construct Reliability (CR). There are 12 items from four dimensions of critical reasoning based on online socio-scientific issues: (1) evaluating SSI information, (2) identifying SSI complexity, (3) checking the credibility of information sources, and (4) multiperspective. The results of the content validity test obtained the Aiken coefficient value in the valid category. Based on the analysis results, the GFI, RMSEA, and p-value of the instrument fit the model and have loading factors that meet the minimum criteria. In addition, the instrument meets convergent validity and internal consistency. Thus, it is concluded that the instrument is declared valid and reliable and can be used to measure critical reasoning based on online socio-scientific issues.